2023
DOI: 10.5455/jabet.2023.d101
|View full text |Cite
|
Sign up to set email alerts
|

Histological and physiological determinants of hypothyroidism in patients and its relationship with lipid profile

Abstract: Hypothyroidism is a disorder in which the thyroid gland does not generate enough thyroid hormone to keep the body operating correctly. Low thyroid hormone levels make it difficult for cells in the body to acquire enough thyroid hormone, causing the body's processes to slow down. There are various reasons why autoimmune illness and radiation therapy are so prevalent. Thyroiditis is caused by too much or too little iodine. Because lipids are hydrophobic (insoluble in water), they cannot transport fats like chole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…We propose that the increase in TG is related to the high activity of the thyroid gland, which consumes a large quantity of TG as a precursor to thyroid hormones. Diana et al [13] indicated an increase in T.G (519 -7 UI/L p≥0.001), Hashim et al [23] indicated an increase in T.G (25.295.83UI/L p 0.001), and El Din et al [13] indicated an increase in T.G (412.88± 142.5 pg/l p 0.001 ) owing for the auto immune's action Abs towards cells of thyroid gland .…”
Section: Tg Between Male and Femalementioning
confidence: 96%
“…We propose that the increase in TG is related to the high activity of the thyroid gland, which consumes a large quantity of TG as a precursor to thyroid hormones. Diana et al [13] indicated an increase in T.G (519 -7 UI/L p≥0.001), Hashim et al [23] indicated an increase in T.G (25.295.83UI/L p 0.001), and El Din et al [13] indicated an increase in T.G (412.88± 142.5 pg/l p 0.001 ) owing for the auto immune's action Abs towards cells of thyroid gland .…”
Section: Tg Between Male and Femalementioning
confidence: 96%